Biomaterials‐Involved Construction of Extracellular Matrices for Tumor Blockade Therapy - Jinfeng Sun; Yang Liu; Jingshan Sun; Jianxun Ding; Xuesi Chen (Exploration)
ABSTRACT Extracellular matrices (ECMs) play a crucial role in the onset and progression of tumors by providing structural support and promoting the proliferation and metastases of tumor cells. Current therapeutic approaches targeting tumor ECMs focus on two main strategies: Inhibiting matrix degradation to prevent metastases and facilitating matrix degradation to enhance the penetration of drugs and immune cells. However, these strategies may lead to unintended consequences, such as tumor growth promotion, drug resistance, and side effects like fibrotic changes in healthy tissues. Biomaterials have made significant progress in fabricating artificial ECMs for tumor therapy by inducing biomineralization, fibrogenesis, or gelation. This perspective explores the fundamental concepts, benefits, and challenges of each technique. Additionally, future improvements and research directions in artificial ECMs are discussed, highlighting their potential to advance tumor therapy.